A study of etiology of fever of unknown origin in children aged 2 months to 18 years - Gandla, Naveen; Bharani, Sheela A.; Shah, Tushar P. (International Journal of Contemporary Pediatrics, 2021)
Background: In an era of advance science of modern technologies, many diseases are diagnosed and excluded rapidly and now Fever of Unknown Origin (FUO) has been redefined for any fever of 380C lasting for more than 7 days without any clear cause. The aetiology varies according to different geographical regions, socioeconomical status, age, prevalence of resistance to antimicrobial drugs and genetic susceptibility. Methods: It was a descriptive cross sectional, hospital-based study, carried out on 150 children from August 2018 to May 2020. All cases in the age group of 2 months to 18 years with fever of >38.0°C, lasting for more than 7 days without a clear source were included. Results: The mean age of presentation was 5.8 years±Standard Deviation of 3.7 years with male to female ratio was 1.4:1. Nearly half of the cases, presented with the duration of fever between 8-14 days. Enteric fever in 52%, tuberculosis in 13.3% and acute lymphoblastic leukemia (ALL) in 8.5% were three common etiologies found in this study. Amongst all cases of FUO, infective causes were seen in 113 (75.3%) followed by malignancies in 15(10%) cases. In 10 (6.7%) cases, cause could not be established. Conclusions: Enteric fever and tuberculosis were the leading etiologies from infective subgroup of FUO. ALL was the commonest cause from malignancies sub group. FUO presenting with low haemoglobin, platelet is a pointer towards malignancy. Occurrence of FUO with infectious diseases and malignancies was found in younger age group as compared to connective tissue diseases.